TRANSGENDER’S ISSUES IN SPORT COMPETITIONS - Petrėnaitė, Daiva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The recognition and development of the rights of transgender people raises various problems, one of which is their possibility to participate in sports. The aim of the article is to identify and analyze the issues of transgenders’ participation in sports, reviewing possible ways of solving them. There used such research methods as analysis of new scientific literature and legal documents, qualitative content and comparative analysis, historical analysis. Study showed that international sports organizations and research bodies do not have a unanimous view how to ensure transgender rights to participate in sports with equality and fairness. New scientific researches may help to change this unclear and ambivalent position as well as established legal regulations and a unified policy of states in this area can help to solve such problems.